Electrical remodelling following percutaneous pulmonary valve implantation in congenital heart disease. (22nd September 2015) - Plymen, CM; Lambiase, P; Bolger, A; Turner, M; Yen Lee, T; Nordmeyer, J; Lurz, P; Coats, L; Taylor, AM; Deanfield, J; Bonhoeffer, P
Abstract : Aims: Sudden cardiac death in congenital heart disease is related to increased right ventricular end diastolic volume (RVEDV), QRS prolongation and abnormalities of QRS, JT and QT dispersions. Surgical pulmonary valve replacement (PVR) and percutaneous pulmonary valve replacement (PPVI) both reduce RVEDV, although the effects of PPVI on surface ECG parameters are unknown. PPVI entails the isolated correction of pulmonary valve lesions independent of direct surgical intervention on the right ventricle, and as such represents a pure model of right ventricular mechanical and electrophysiological changes post-PVR. Surgical studies have so far failed to show consensus on significant changes in QRS duration post-procedure, and have shown no significant changes in QRS or QT dispersion values, possibly due to the direct effects of surgery on the right ventricular myocardium. This prospective study therefore sought to determine the effects of PPVI on QRS duration and QRS, JT and QT dispersion values. Methods: 109 PPVI patients with congenital heart disease (aged 22.9 ± 10.6 years) were studied preprocedure, at 24 h and 1 year postoperatively with transthoracic echocardiography and cardiac magnetic resonance imaging and additionally at 3 and 6 months with ECG. 55% had pulmonary stenosis, 27% pulmonary regurgitation and 19% mixed lesions. Diagnosis included pulmonary atresia (30%), tetralogy of Fallot (28%), transposition of the creat arteries (12%), truncus arteriosus (12%), congenital aortic or pulmonary valve disease (15%) and double outlet right ventricle (3%). Results: QTc, QRSd, QTd and JTd all showed significant reductions at one year (p<0.0001; fig 1). Patients over 17 years of age had significant improvement in QRSd, QTd, JTd and QTc compared with those aged under 17 years (p = 0.0023). Patients with stenotic lesions had a non-significant trend towards greater post-procedure reductions; however, only JTd reached significance (p = 0.026). QRS duration did not change (p = 0.73) although it did stabilise at one year (138 ± 28 to 137 ± 28 ms). Although RVEDV correlates to preprocedure QRS duration (p<0.0001) there is no correlation when comparing the changes seen over one year (p = 0.76). For the whole group RVEDV, right ventricular end systolic volume and right ventricular systolic pressure decreased significantly (7.58%, 10.75%, 22.04% decrease, respectively, p<0.0001). Conclusions: PPVI represents a pure model of relief from the haemodynamic consequences of right ventricular stretch compared with its surgical counterpart. This is the first study reporting electrical remodelling following isolated pulmonary valve replacement, and it confirms that right ventricular haemodynamics significantly improve post-PPVI. QRS duration shows no significant change. However, QTc, QTd, QRSd and JTd significantly improve at one year follow-up. Older patients and those with stenotic valvar lesions have greater changes in ECG parameters (fig 2). This study suggests that PPVI is associated with electrocardiographic remodelling to a greater degree than reported in surgical PVR.